Sustainable development of tyre char-based activated carbons with different textural properties for value-added applications. (1st April 2016) - Hadi, Pejman; Yeung, Kit Ying; Guo, Jiaxin; Wang, Huaimin; McKay, Gordon
Abstract: This paper aims at the sustainable development of activated carbons for value-added applications from the waste tyre pyrolysis product, tyre char, in order to make pyrolysis economically favorable. Two activation process parameters, activation temperature (900, 925, 950 and 975 °C) and residence time (2, 4 and 6 h) with steam as the activating agent have been investigated. The textural properties of the produced tyre char activated carbons have been characterized by nitrogen adsorption–desorption experiments at −196 °C. The activation process has resulted in the production of mesoporous activated carbons confirmed by the existence of hysteresis loops in the N2 adsorption–desorption curves and the pore size distribution curves obtained from BJH method. The BET surface area, total pore volume and mesopore volume of the activated carbons from tyre char have been improved to 732 m 2 /g, 0.91 cm 3 /g and 0.89 cm 3 /g, respectively. It has been observed that the BET surface area, mesopore volume and total pore volume increased linearly with burnoff during activation in the range of experimental parameters studied. Thus, yield-normalized surface area, defined as the surface area of the activated carbon per gram of the precursor, has been introduced to optimize the activation conditions. Accordingly, the optimized activation conditions have been demonstrated as an activation temperature of 975 °C and an activation time of 4 h. Highlights: Activated carbons were sustainably produced from tyre char. The synthesized activated materials were thoroughly characterized. Yield-Normalized surface area was used for optimum activation conditions. Highest yield-normalized surface area was obtained at 975 °C for 4 h.